Lie hard [videorecording (Blu-Ray)] - Chandra, Melanie; Curtin, Catherine; Garland, Joel Marsh (Mutiny Pictures, Inc., 2021)
To impress his girlfriend's wealthy parents, a pathological liar borrows 4 million dollars from a crime syndicate to purchase a mansion. Unfortunately for him, all debts need to be paid back.